Mortality outcomes and 30-day readmissions associated with coronary artery aneurysms; a National Database Study. (1st June 2022) - Mir, Tanveer; Uddin, Mohammed; Changal, Khalid; Qureshi, Waqas; Weinberger, Jarrett; Wani, Javed; Maganti, Kameswari; Rab, Tanveer; Eltahawy, Ehab; Sheikh, Mujeeb
Abstract: Background: The literature on prevalence and outcomes of coronary artery aneurysm (CAA) in the United States (US) is limited. Objective: To study the prevalence, outcomes, and trends of CAA. Methods: Data from the national readmissions database (NRD) sample that constitutes 49.1% of the stratified sample of all hospitals in the US were analyzed for CAA among coronary angiography (CA) related hospitalizations for the years 2012–2018. Results: A total of 6, 843, 910 index CA related hospitalizations were recorded for the years 2012–2018 in the NRD (Mean age 64.37 ± 13.30 years' 38.6% females). Of these 9671 (0.141%) were CAA, 5092 (52.7%) without-ACS and 4579 (47.3%) with ACS [NSTEMI occurred in 2907(63.5%) and STEMI in 1672(36.5%)]. In-hospital mortality among CAA was comparable to those without-CAA on angiography (n-209, 2.17% vs n  = 175, 120, 2.56%; p  = 0.08). CAA patients who presented with ACS vs those without ACS had higher mortality ( n  = 150, 3.28%vsn = 60, 1.16%; p  < 0.001) cardiogenic shock 6.9%vs2%, ventricular arrythmias 9.2%vs5.2%, coronary dissection 58%vs42.7%, and need for mechanical circulatory support 7%vs2.7% respectively. Percutaneous coronary intervention (PCI) was performed among 45.2% patients; however, on coarsened exact matching of baseline characteristics, PCI had no association with mortality, patients (OR 1.22, 95%CI0.69–2.16, p  = 0.49). The prevalence of CAA on CA trend towards increased mortality with ACS increased over the years 2012–2018 (linear p-trend <0.05). The 30-day readmissions rate were 13.8% (non-CAA) vs 4.6% (CAA) p  = 0.001 predominantly cardiovascular causes (50.9%vs70.7%) and PCI on readmission (7.06%vs17.5%). Conclusion: CAA is an uncommon anomaly noted on coronary angiography. The higher mortality in patients with ACS and increasing trend of CAA-ACS warrants more research. Graphical abstract: Central Illustration. Graphical representation for the possible complications associated with coronary artery aneurysm patients with acute coronary syndrome. (Created with Biorender.com ). Unlabelled Image Highlights: The prevalence of CAA was 14 per 10, 000 coronary angiographies in NRD 2012-2018. Patients with acute MI and CAA had higher mortality rates and higher need for mechanical circulatory support. CAA trend increased over 2012-2018 as did the mortality in patients within ACS subgroup of CAA. CAA patients had lower rates of 30-day readmissions, however, higher rates of PCI on readmission. Half of the patients with CAA had associated spontaneous coronary artery dissection recorded in the hospitalization encounters.